KEMAMPUAN MENULIS HASIL OBSERVASI DALAM BENTUK PARAGRAF DESKRIPSI - Fitriyani, Dwi; Kusniati, Ana Wahyu (Pesona, 2019)
The result of preliminary research in SMA N 1 Air Naningan showed that students tenth class ability in writing paragraph have difficulties in determining topic, producing and developing frame of thinking, error in spelling Indonesian language. Objective of this research is to know students? ability in writing paragraph observation result in writing descriptive paragraph. Methodology of research used is descriptive. The data analysis used was essay test which is measured by using the formula which related to the assessment indicator. The result of the research showed percentage score 67 from average score of students? abilities at eight grade of first semester at SMA N I Air Naningan Tanggamus in the academic years 2017-2018 was enough categorized.  The students of SMAN 1 Air Naningan?s ability in writing descriptive text was categories as enough because they were not  enthusiasm to read the books which were related to descriptive text, uninterested media and method used by the teacher in the learning process, and limit reference which was available in the library.